Effect of Five Finger Hypnosis Anxiety Hypertension Clients at Puskesmas Neglasari, Tangerang City - Dalami, Ermawati; Nasihin, Nasihin; Subiakto, Toto (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
Background: hypertension is a disorder of the blood vessels that has become a problem in both developed and developing countries, clients with hypertension can cause anxiety (anxiety). One of the interventions to reduce anxiety levels is the five finger hypnotic therapy technique. Purpose : determine the effect of five finger hypnosis on anxiety (anxiety) at Nelasari Health Center, Tangerang City, Banten. Methodology : uses a quasi-experimental design (pseudo-experiment) with a pre-test post-test equivalent control group design approach. Results : showed that there was a change (decrease) in the mean anxiety score between the intervention group, namely (7.19), when compared to the control group, namely (1.52). Based on the results of the Normality test, it was found that the change in anxiety scores in each group was not normally distributed (p = 0.000 or p <α), so the test used was the Mann-Whitney Non-Parametric Test and obtained a value of p = 0.000 (p <α) which means there is a difference statistically significant from the magnitude of the change (decrease) in the average anxiety score between the two groups, it can be interpreted that in the intervention treatment group the influence of five finger hypnosis was very dominant in reducing anxiety compared to the control group in the Neglasari Health Center area. Conclusion : Five-finger hypnosis has a significant effect on reducing anxiety in hypertensive clients. Suggestions, it is hoped that the five finger hypnotic therapeutic intervention will be an alternative intervention that can be applied in nursing services.